(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The word myth has been taken from Greek word mythos; mythmeans story or word. Mythology is the study of myth. It means a fairy tale,“something false” or “imagination” or “Unbelievable”. The English term mythderived from the Greek mythos, means “word” or speech” “the thing spoken”, “thetale told” perhaps any information transmitted verbally including both “truthand false”. As stories, myths articulate how character undergo or exact anordered sequence of events. The term myth has come to refer to a certain genreof stories that share characteristics that make this genre distinctly differentfrom other genres of oral narratives, such as legends and folktales manydefinitions of myth repeat similarly general aspects of the genre and may besummarized thus ; myths are symbolic tales of the distant past that concerncosmogony and cosmology (the origin and nature of the universe), may beconnected to belief systems or rituals, and may serve to direct social actions’and values. There are many concepts regarding myths. Myths are cosmogonynarratives, connected with the foundation or origin of the universe, thoughoften specifically in terms of a particular culture or region. Myths arenarratives of a sacred nature, often connected with some ritual. Myths areoften foundational or key narratives associated with religions. Myth narrativesoften invoice heroic character that mediate inherent troubling dualitiesreconcile us to our realities, or establish the patterns for life as we knowit. There have been many other functions and implications attributed to myth.They are often highly valued or disputed stories that still intrigue us eventhough many of us do not. Recognize them as a living genre in our culture. McDowell says myths are often involve extraordinary characters or episodes thatseem impossible in our world but the extraordinary feats and traits of mythicprotagonists are possible only because they attach to a primary and formativeperiod in the growth and development of civilization. Thus their variousaspects or dimensions are best considered as “organically intertwined”. Mythsalso seem in opposition to science because they are not testable, which is thecase because of their primordial setting-If events described are from adifferent earlier world, then of course they would not be repeatable or logicalin our world.